2013
DOI: 10.4025/actascianimsci.v35i3.18290
|View full text |Cite
|
Sign up to set email alerts
|

<b>Can a small change in the tilapia’s on-going feeding strategy impair its growth?</b> - doi: 10.4025/actascianimsci.v35i3.18290

Abstract: ABSTRACT. The aim of the present work was to answer the following question: can a small change in the tilapia's on-going feeding strategy impair its growth? In the initial phase of the study, fish were evenly distributed and maintained for two weeks in four tanks. In tanks 1 and 2, the ration was given in three equal meals at 8, 12 and 16h or at 9, 13 and 17h, respectively. In tanks 3 and 4, there was only one daily meal at 9 or 10 o'clock, respectively. In the second 8-week phase, fish from tank 1 were distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…These results clearly indicate that fish growth is also significantly and positively correlated with the trophic status of the ponds. These results are similar to those obtained by many other workers (See: Garg & Bhatnagar, , ; Caldini et al., for references).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results clearly indicate that fish growth is also significantly and positively correlated with the trophic status of the ponds. These results are similar to those obtained by many other workers (See: Garg & Bhatnagar, , ; Caldini et al., for references).…”
Section: Discussionsupporting
confidence: 93%
“…(), Caldini et al. () and Mattos, Filho, Barreto et al.,; Mattos, Filho, Santos et al.,(). It may be concluded that investigations on meal timings are important to obtain better growth performance.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations